Beyond the mind : cultural dynamics of the psyche - Marsico, Giuseppina; Valsiner, Jaan (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
"This book Beyond the Mind: Cultural Dynamics of the Psyche is unusual in the content and it the format. That's why it requires an unusual look. It has to do with a man, an intellectual journey and with uncountable travels across the world over the last two decades. This man is Jaan Valsiner and here you will read of his restless effort of elaborating ideas while going in different places as invited keynote. This book is mainly about his intellectual trajectory, which touches several places and several and interconnected topics. This book is about the "minutes" of his "bigger" and well organize works and also it is a collection of only apparently fragmented texts (mainly keynote lectures, unpublished or rejected papers) where the readers will see the "step- by-step" elaboration over the years of new ideas, theories, models and even schemas (which Jaan likes very much--maybe especially as he claims basic inability to draw anything)"-- Provided by publisher.
Keywords: Valsiner, Jaan.; Culture -- Psychological aspects.; Psychology -- General.; Psychology.; elektronické knihy; electronic books